Risk Factors of Covid-19 Confirmed Died Patients in Dr. Kariadi Hospital: A Retrospective Study - Sulistyowati, Elyana Sri; Muninggar, Septi Sewi; Silalahi, Verarica (Indonesian Journal of Tropical and Infectious Disease, 2021)
Covid-19 is a communicable disease causing global pandemic. Some factors inflict worse infection. This study aims to investigate risk factors of Covid-19 confirmed died patients at Dr. Kariadi Hospital Semarang. It is a retrospective study with a total sample of all Covid-19 confirmed patients involving died and healed patients from March to June 2020. Data was gathered from screening forms and analysed with Chi Square (confidence interval of 95%). This study found sixteen risk factors of Covid-19 confirmed died patients involving age (p= 0.000; OR= 8.803; 95% CI 3.982-19.462), entrepreneur (p= 0.041; OR= 14.894; 95% CI 1.12-198.65), farmer/trader (p= 0.029; OR= 25.625; 95% CI 1.40-469.25), contact history (p= 0.000; OR= 12.923; 95% CI 6.163-27.097), fever (p= 0.000; OR= 4.877; 95% CI 2.647-8.984), dyspnea (p=0.000; OR= 17.018; 95% CI 8.523-33.977), cough (p= 0.009; OR= 2.178; 95% CI 1.205-3.935), lethargic (p=0.010; OR= 2.282; 95% CI 1.205-4.323), cold (p= 0.002; OR= 0.180; 95% CI 0.054-0.600), diabetes (p=0.000; OR= 9.767; 95% CI 3.932-24.263), COPD (p= 0.001; OR= 6.360; 95% CI 2.164-18.690), hypertension (p= 0.043; OR= 2.436; 95% CI 1.008-5.887), cancer (p=0.001; OR= 9.647; 95% CI 2.413-38.579), heart disease (p= 0.000; OR= 12.226; 95% CI 2.4-62.294), neurological disorders (p=0.008; OR= 6.057; 95% CI 1.650-22.232), and immune disorders (p=0.031; OR= 1.625; 95% CI 1.186-113.899). Adequate handling is needed to prevent death. in patients with confirmed Covid-19 who have risk factors.